Harry Potter and the cursed child. Parts one and two - Rowling, J. K.; Thorne, Jack; Thorne, Jack; Tiffany, John, 1971- (Arthur A. Levine Books, an imprint of Scholastic Inc., 2016)
As an overworked employee of the Ministry of Magic, a husband, and a father, Harry Potter struggles with a past that refuses to stay where it belongs while his youngest son, Albus, finds the weight of the family legacy difficult to bear.